DEWAN PERWAKILAN RAKYAT SEBELUM DAN SESUDAH AMENDEMEN UNDANG-UNDANG DASAR NEGARA REPUBLIK INDONESIA TAHUN 1945 - Merina Nurmiati; Dodi Haryono; Emilda Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
The People's Representative Council is an organ that exercises direct legislative powers in the 1945 constitution. The phenomena that occurred during the New Order era tended to benefit the executive branch. The House of Representatives of the people of the new order is only used as a "stamp institution" against government policies that deviate more and contrary to Pancasila and the law. The implementation of the budget function and the function of legislation, the People's Legislative Assembly shall always follow the will of the authorities so that the supervisory function is not effective. With the fall of the New Order regime by the reform movement of 1998 and the amendment to the 1945 Constitution, especially regarding the institutionalization of the People's Representative Council, the authority of the House of Representatives has changed. The purpose of writing this thesis are: First, to know the function of oversight of the House of Representatives before and after the amendment of the 1945 Constitution of the State. Secondly, to know the weaknesses and advantages of supervisory functions before and after the amendment. Third, to know the optimization of supervision function after amendment. This type of research can be categorized into normative legal research. Data type used primary data, secondary and tertiary data. The three main points that can be concluded are: First, before the amendment of the 1945 Constitution, the scope of the DPR's oversight function implicitly the state budget, establishes the law, The right to file an opinion, the right to file / suggest a person, the right to file a bill. After the amendment , the scope of Supervising the approval of APBN, Act and government policies, besides that the DPR can give consideration to appoint ambassadors and placement of ambassadors as well as granting amnesty and abolition. Second, weakness prior to amendment of weak supervision on prerogative right of appointment of ambassador, acceptance of other country ambassadors and appointment and dismissal of police chief and granting pardon, amnesty, abolition and rehabilitation, The role of the House of Representatives in supervision, forming a supporting instrument for supervisory function, improving supervisory performance Author suggestion Firstly, it is necessary to oversee the performance of DPR from independent bodies; Secondly, it is necessary to improve the performance of DPR.Keywords: Amendment - DPR - Monitoring function